Intravenous Thrombolysis Increases the First Pass Effect for Large Vessel Occlusion Treated With Mechanical Thrombectomy - Yuki Kamiya; Kentaro Suzuki; Yoshifumi Miyauchi; Ayako Kuriki,; Keita Mizuma; Wataro Tsuruta; Yuji Matsumaru; Kazumi Kimura (Stroke: Vascular and Interventional Neurology, 2023)
Background It remains unclear whether intravenous thrombolysis (IVT) influences the incidence of the first pass effect (FPE) in patients with acute large vessel occlusion treated with mechanical thrombectomy (MT). Therefore, this study investigated the effects of IVT on FPE in patients treated with MT. Methods This is a post hoc analysis of the SKIP (Direct Mechanical Thrombectomy in Acute LVO Stroke) study, which was an investigator‐initiated, multicenter, randomized, open‐label clinical trial performed in 23 hospital networks in Japan from January 1, 2017, to July 31, 2019. Among 204 patients, 24 were excluded because they did not undergo MT. Patients treated with MT alone were compared with those treated with MT+IVT for the incidence of FPE (achieving a modified treatment in cerebral ischemia score of 2c or 3 after the first MT pass). Additional subgroup analyses were performed to investigate factors more closely related to the association between IVT and FPE. Results Among the 180 patients, 91 were treated with MT alone and 89 were treated with MT+IVT. FPE was achieved in 56 patients (31.1%). The incidence of FPE was significantly higher in patients treated with MT+IVT than in those treated with MT alone (39.3% versus 23.0%, respectively; P=0.02). In the subgroup analyses, IVT markedly increased FPE in female patients and tended to increase FPE in patients with first‐segment middle cerebral artery distal occlusion and onset to hospital arrival time >100 minutes. Conclusion IVT using alteplase increased the incidence of FPE in Japanese patients with acute ischemic stroke treated with MT. Trial Registration : Trial registration umin.ac.jp/ctr identifier: UMIN000021488